2020
DOI: 10.1115/1.4047663
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Vortex Alterations With Reducing Left Ventricular Volume: An In Vitro Study

Abstract: Despite the large number of studies of intraventricular filling dynamics for potential clinical applications, little is known as to how the diastolic vortex ring properties are altered with reduction in internal volume of the cardiac left ventricle (LV). The latter is of particular importance in LV diastolic dysfunction and in congenital diseases such as hypertrophic cardiomyopathy (HCM), where LV hypertrophy can reduce LV internal volume. We hypothesized that peak circulation and the rate of decay of circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Reduced vortex size and delayed vortex formation time was observed in patients and confirmed in models simulating left ventricular hypertrophy (27,28). These findings were attributed to the reduced LV volume not providing sufficient space for proper vortex development, ultimately resulting in increased kinetic energy dissipation (27,28). Hence, extrapolating these findings to our study of healthy porcine hearts, it could be argued that RCC regurgitant jets induced a "fluid dynamic" correlate to reduction of space available for proper diastolic vortex development in hypertrophic left ventricle.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Reduced vortex size and delayed vortex formation time was observed in patients and confirmed in models simulating left ventricular hypertrophy (27,28). These findings were attributed to the reduced LV volume not providing sufficient space for proper vortex development, ultimately resulting in increased kinetic energy dissipation (27,28). Hence, extrapolating these findings to our study of healthy porcine hearts, it could be argued that RCC regurgitant jets induced a "fluid dynamic" correlate to reduction of space available for proper diastolic vortex development in hypertrophic left ventricle.…”
Section: Discussionmentioning
confidence: 52%
“…On the other hand, RCC jets were directed along the septal wall and locally reduced the cross-sectional size of the vortex delaying or even prohibiting vortex formation. Reduced vortex size and delayed vortex formation time was observed in patients and confirmed in models simulating left ventricular hypertrophy (27,28). These findings were attributed to the reduced LV volume not providing sufficient space for proper vortex development, ultimately resulting in increased kinetic energy dissipation (27,28).…”
Section: Discussionmentioning
confidence: 75%
“…This is in accordance with previous biomechanical studies which demonstrated that reducing end-diastolic volumes in a physical left heart simulator led to increased size and dynamics of the LV vortex. [18] In addition, our study found that sphericity index increased with decreasing LVEDVi, suggesting that the vortex became more long-stretched once the ventricle was smaller. Together, these findings suggest that LV shape and internal volume play a critical role in determining vortex dimensions and dynamics, potentially due to the increased confinement associated with smaller intraventricular volumes.…”
Section: Discussionmentioning
confidence: 55%
“…The Γ of the LEV or TEV was then calculated by selecting a region of interest (ROI) by drawing a box around a vortex core. A custom MATLAB script was used to automate the process of determining the ROI (Samaee et al 2020). Essentially, we started with a small square box of 2 mm side and compared the Γ value with that of a bigger square box of 5 mm side.…”
Section: Flow Visualizationmentioning
confidence: 99%